2022
DOI: 10.1002/cctc.202200440
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Bromide Catalyzed Ligand‐Free and Activator‐less Suzuki Coupling Reactions

Abstract: Readily available and inexpensive bromide salt based on earthabundant nickel has been used to catalyze the Suzuki coupling of a variety of aryl halides (ca. 37 examples) in high yields under ambient conditions with good functional group tolerance. The reactivity of various aryl halides follows the corresponding CÀ X (X = I, Br and Cl) bond strength in the order ArÀ I > ArÀ Br > ArÀ Cl. EPR analysis, mercury-drop experiments and reactions with radical scavenger such as TEMPO point to the involvement of well-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…Meanwhile, Kumar et al reported the SM coupling reaction of aryl halides using NiBr 2 (8 mol%) as the catalyst. 59 Although their method provided yields of up to 92% with aryl bromides and iodides, it only provided yields of up to 42% with aryl chlorides. Doyle et al have reported comparison studies of monophosphine and bisphosphine ligands for the Ni-catalyzed SM reactions of aryl chlorides (Scheme 17 ).…”
Section: Suzuki–miyaura Cross-couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Kumar et al reported the SM coupling reaction of aryl halides using NiBr 2 (8 mol%) as the catalyst. 59 Although their method provided yields of up to 92% with aryl bromides and iodides, it only provided yields of up to 42% with aryl chlorides. Doyle et al have reported comparison studies of monophosphine and bisphosphine ligands for the Ni-catalyzed SM reactions of aryl chlorides (Scheme 17 ).…”
Section: Suzuki–miyaura Cross-couplingmentioning
confidence: 99%
“…Meanwhile, Kumar et al reported the SM coupling reaction of aryl halides using NiBr 2 (8 mol%) as the catalyst. 59 Although their method provided yields of up to 92% with aryl bromides and iodides, it only provided yields of up to 42% 60 Although bisphosphine-type ligands are typically used for nickel-catalyzed SM reactions, the results suggested that monomeric phosphine ligands (e.g., CyTyrannoPhos) might outperform bisphosphine ligands depending on the nature of the substrates. They proposed that monophosphine ligands enabled challenging oxidative addition and transmetalation steps, whereas bisphosphine ligands prevented off-cycle reactivity and catalyst deactivation.…”
Section: Scheme 15 Synthesis Of a Biphenyl Sartan On Gram Scalementioning
confidence: 99%
“…The fluorescence efficiency and the electronic properties of the molecules depend on the geometry of the molecules . The rigid polycyclic aromatic hydrocarbons (PAHs) , exhibit high fluorescence efficiency, which can be controlled by the addition of substituents like amino, amino acid ester, aryl, carboxylic acid, and hetero atoms. , Addition of polyethynylated units to the PAHs enhances the π-conjugation, which helps to decrease the band gap, lowering the torsional barrier and enhancing the thermal stability, which are favorable for the fabrication of such compounds in optoelectronic devices . The polyalkynylated unit can be introduced to the PAHs by the Sonogashira reaction.…”
Section: Introductionmentioning
confidence: 99%